2012
DOI: 10.1007/s00393-012-1058-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and insulin resistance comorbidity in systemic lupus erythematosus

Abstract: Insulin sensitivity and IMT are altered in SLE patients, especially those with MetS comorbidity with an associated increase in disease activity and damage. Effective management of MetS would help control SLE activity, damage, and the future development of cardiovascular events especially in the absence of symptoms of cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…The increased IMT in SLE in the present study has been confirmed in several studies [24][25][26]. Furthermore, in other studies on Egyptian SLE patients, the IMT was found to be significantly increased [11,12,27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The increased IMT in SLE in the present study has been confirmed in several studies [24][25][26]. Furthermore, in other studies on Egyptian SLE patients, the IMT was found to be significantly increased [11,12,27].…”
Section: Discussionsupporting
confidence: 91%
“…The IMT has been found to be increased in many rheumatic diseases such as rheumatoid arthritis [10], SLE [11,12], Behcets disease [13] and osteoarthritis [14]. Together with classical conventional risk factors, other mechanisms (disease-specific factors) promote accelerated atherosclerosis in SLE.…”
Section: Introductionmentioning
confidence: 98%
“…Icli et al [11] and Ammirati et al [23] showed that cIMT values were higher in SLE patients compared to control individuals. Gheito et al [24] demonstrated that cIMT levels were higher in SLE patients than in their control group and that it showed a correlation with SLEDAI. Batún Garrido et al [5] reported the strong correlation between SLE activity and dyslipidemia.…”
Section: Discussionmentioning
confidence: 95%
“…In Negrón et al [17], SLAM-R-scored SLE activity was independently associated with MetS (OR 1.14; 95 % CI 1.00-1.30). In Gheita et al [32], SLEDAI and SLICC were significantly increased in SLE patients, especially those with MetS, and the carotid intima-media thickness correlated with disease activity. However, since all the studies evaluating this relation were cross-sectional, they were limited to establishing associations between variables, not causality.…”
Section: Discussionmentioning
confidence: 96%
“…Age and disease duration are clearly positively associated with MetS since the likelihood of developing this condition increases over time of exposure to disease-specific inflammatory and metabolic mechanisms and therapy. Damage has been associated with MetS in several studies [17,18,[20][21][22]32]. A meta-analysis by Sun et al [33] including 56,691 individuals from the general population and 8688 cases of MetS showed that active smoking increased the risk of MetS by 26 %.…”
Section: Discussionmentioning
confidence: 97%